System Water Purifier With Arduino Based PID Control - Permana, Dani; Widya Sari, Marti; Hardyanto, R. Hafid (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2022)
Dirty water can endanger the health and mental safety of humans, which can lead to outbreaks of cholera, ringworm, scabies, diarrhea/dysentery, and typhoid which are some of the diseases that arise from dirty water which are still consumed without further processing. To deal with dirty water, researchers have a solution with a water filtering system using a water purification system with an Arduino- based Pid sensor control, where the water will be filtered in the water treatment then the water will be detected by the LDR sensor is still cloudy or clean, if the water is still cloudy, Arduino will send the command to relay to turn on the water pump so that the water will flow back to the water treatment. if the water is clean, the water will be put into the container that has been provided. Then the results from the water will be displayed in the application that was made using the Inventor app. Verify the results of system testing that the application is running very well when displaying the results of the system being created.